ANALISIS PELAKSANAAN PEMUNGUTAN RETRIBUSI TEMPAT KHUSUS PARKIR DAN RETRIBUSI PARKIR DI TEPI JALAN UMUM SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KOTA PADANGSIDIMPUAN - Irfan Fajri Rambe; Budiman Ginting; Mirza Nasution; Jusmadi Sikumbang (Universitas Sumatera Utara, 2018)
ABSTRACT An analysis of the implementation of retribution of parking-specific levies and public parking levies as a source of revenue for Padangsidimpuan city is how the arrangement, implementation, constraints and solutions in levies retribution of parking lots and public roadside parking as an effort to increase local revenue since the enactment regional autonomy. Levies of special parking spaces and public roadside parking are distinguished by the management and location of the parking. The problem in this research concerns how the arrangement of retribution levy of parking at public roadside and special place of parking as source of original income of Padangsidimpuan city?, how policy implementation which have been done by Padangsidimpuan city government in exploring potency of PAD through parking levy on public road and where special parking?, and how the curbing of the implementation of parking management proven violate the city regulation Padangsidimpuan no. 4 of 2010 and No. 5 of 2010?. This research is analyzed using fiscal decentralization theory and legal system theory. The research method is normative legal research method and is analytical descriptive with primary, secondary and tertiary legal material with technique and data collection tool, namely: library research and document study and interview. The regulation of parking fee retribution procedure shall be stipulated by regional regulation and regulation of regional head. Levies are collected by using SKRD or other equivalent documents. Padangsidimpuan municipal government policy to explore the potential of local revenue (PAD) through the collection of public roadside parking levies and special places of parking is regulated in Local Regulation Padangsidimpuan city no. 4 of 2010 on Public Service Business Levies and Local Regulations Padangsidimpuan city no. 5 of 2010 on Service Levies. the implementation of collection of parking fees is managed by the Department of Transportation Padangsidimpuan city. Efforts of Padangsidimpuan city government in order to implement parking management in violation of the provisions of City Regulation Padangsidimpuan no. 4 of 2010 and Regional Regulation of Padangsidimpuan no. 5 of 2010 by the local government through the Department of Transportation of Padangsidimpuan City oversees the management of parking and controlling through the imposition of sanctions.Keywords: Levy Collection Analysis, Special Parking Area, Parking On Public Road, Local Revenue, Padangsidimpuan City